2006
DOI: 10.14411/eje.2006.090
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cold hardiness by acclimation is stage-specific in the non-diapausing pupae of onion maggot Delia antiqua (Diptera: Anthomyiidae)

Abstract: Abstract. When puparia of the onion maggot Delia antiqua were preexposed to 5°C for 5 days starting at different time points after pupariation, a large increase in survival after exposure to -20°C for 5 days was observed only when pre-exposure was initiated at 3-6 days after pupariation. The increase in cold hardiness was not associated with a large increase in the trehalose content of the puparia. The supercooling point of the puparia naturally decreased from -18 to -27°C in the first three days after puparia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This relationship suggests that trehalose plays an important role in the overwintering strategy of the codling moth. Trehalose, the major insect blood sugar, has previously been considered a cryoprotectant in some insect species (Storey & Storey, 1991;Rojas et al, 1994;Koš ál & Šimek, 1995Koš ál & Šimek, , 1996Goto et al, 2001;Koš ál et al, 2001;Nomura & Ishikawa, 2001), but not in others (Naeemullah et al, 1999;Miyazaki et al, 2006). Despite widespread interest in cryoprotection, the mechanism by which trehalose confers cryoprotection is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship suggests that trehalose plays an important role in the overwintering strategy of the codling moth. Trehalose, the major insect blood sugar, has previously been considered a cryoprotectant in some insect species (Storey & Storey, 1991;Rojas et al, 1994;Koš ál & Šimek, 1995Koš ál & Šimek, , 1996Goto et al, 2001;Koš ál et al, 2001;Nomura & Ishikawa, 2001), but not in others (Naeemullah et al, 1999;Miyazaki et al, 2006). Despite widespread interest in cryoprotection, the mechanism by which trehalose confers cryoprotection is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In D. antiqua, the increase in cold hardiness was not associated with a large increase of cryoprotectants, including trehalose, in the puparia (Miyazaki et al, 2006). Recently, Chen et al (2005Chen et al ( , 2006 reported that heat shock proteins (HSP90 and HSP70), which facilitate renaturation of proteins after stress, are upregulated in SD and WD pupae.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of summer-diapause (SD) and winter-diapause (WD) pupae after a 5 days exposure to À20 1C exceeds 75%. Meanwhile, non-diapausing pupae also show a significantly increased survival rate when they are pre-exposed to 5 1C (cold-acclimated non-diapause pupae, CA) Miyazaki et al, 2006). We have long been interested in the mechanism of strong cold hardiness in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, non-diapausing pupae also show a significantly increased survival rate when they are preexposed to 5°C (cold-acclimated non-diapause pupae, CA) ( Fig. 1 ) [25] , [26] . To explore the molecular mechanisms underlying the strong hardiness in D. antiqua , we sought for differentially expressed genes in the cold-acclimated and diapause pupae.…”
Section: Introductionmentioning
confidence: 99%